BNIP3-mediated mitophagy aggravates placental injury in preeclampsia via NLRP1 inflammasome - Zhao, Man; Yang, Zexin; Kang, Yan; Fang, Zhenya; Zhang, Changqing; Wang, Chunying; Zhou, Meijuan; Guo, Junjun; Li, Anna; Zhang, Meihua (Frontiers in Immunology, 2025)
IntroductionPreeclampsia (PE) is a hypertensive disorder of pregnancy characterized by pronounced placental oxidative stress and inflammatory damage. However, the contribution of mitophagy to inflammation-induced placental injury in PE remains unclear. MethodsHuman placenta samples were collected from 15 normal pregnant women and 15 preeclampsia pregnant women. Protein expression was analyzed by western blotting, while immunofluorescence staining was employed to localize inflammatory mediators. Mitochondrial reactive oxygen species were quantified using MitoSOX. The concentrations of pro-inflammatory cytokines were quantified using ELISA, and ultrastructural alterations were evaluated by transmission electron microscopy. To investigate molecular mechanisms in vivo, a PE mouse model was established via daily subcutaneous administration of L-NAME, followed by tail vein delivery of AAV9 carrying shRNA for targeted gene knockdown. ResultsIn this study, we demonstrate that BNIP3-mediated mitophagy and NLRP1 inflammasome activation occur in an L-NAME-induced PE mouse model and human PE placenta. The results also indicate that knockdown of BNIP3 abolishes mitophagy and NLRP1 inflammasome activation in JEG3 cells in H/R condition, suggesting a positive regulatory role for the BNIP3 in controlling mitophagy and NLRP1-dependent inflammation. Furthermore, silencing BNIP3 leads to a significant reduction in mitochondrial damage and mtROS production. Treatment with MitoTEMPO after BNIP3 silencing further decreases the expression of NLRP1, while overexpression of NLRP1 nullifies the impact of BNIP3 knockdown. Additionally, knockdown of BNIP3 alleviates placental injury in the PE mouse model. DiscussionThese findings reveal a novel mechanism through which BNIP3-mediated mitophagy exacerbates H/R-induced placental injury by inducing mtROS production and activating the NLRP1 inflammasome in PE.